2015
DOI: 10.4025/actascianimsci.v37i3.24980
|View full text |Cite
|
Sign up to set email alerts
|

<b>Estimates of <i>in situ</i> digestibility and fibrous compounds in feeds for ruminants

Abstract: ABSTRACT. Current paper assesses the relationship between in situ incubation time, particle size and types of materials on estimates of indigestible fractions of dry matter (iDM) and neutral detergent fiber (iNDF) in cattle feed and feces. Samples of soybean meal, alfalfa and feces of cattle fed on high concentrated diets were analyzed. The samples were processed in a Wiley mill, with 0.5 and 1.5 mm porosity for food and 1.5 mm for feces, which were packed in 4 × 5 cm F57 bags (Ankon ® ) and nonwoven fabric (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…They also reported that iDM fraction is made up of essentially insoluble components, similar to the iDF and iADF fractions. Although data in current experiment corroborate the theory by Casali et al (2008), Kuwahara et al (2015) reported that more intense grindings may overestimate iDM and iNDF rates at an average of 6.57% for alfafa when grinding shifted from 1.5 mm to 0.5 mm for a fixed period of 240 hours. When the concept by Mertens (1993), previously discussed, is taken into consideration, coupled to the description by Detmann et al (2008) as a slightly precise concept, results of current analysis (Figure 2 and Tables 2 and 3) reveal that the nylon textile in the three grindings had lower iDM and iNDF rates when compared to other treatments (p < 0.05) in the initial period of incubation.…”
Section: Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…They also reported that iDM fraction is made up of essentially insoluble components, similar to the iDF and iADF fractions. Although data in current experiment corroborate the theory by Casali et al (2008), Kuwahara et al (2015) reported that more intense grindings may overestimate iDM and iNDF rates at an average of 6.57% for alfafa when grinding shifted from 1.5 mm to 0.5 mm for a fixed period of 240 hours. When the concept by Mertens (1993), previously discussed, is taken into consideration, coupled to the description by Detmann et al (2008) as a slightly precise concept, results of current analysis (Figure 2 and Tables 2 and 3) reveal that the nylon textile in the three grindings had lower iDM and iNDF rates when compared to other treatments (p < 0.05) in the initial period of incubation.…”
Section: Methodssupporting
confidence: 78%
“…When the concept by Mertens (1993), previously discussed, is taken into consideration, coupled to the description by Detmann et al (2008) as a slightly precise concept, results of current analysis (Figure 2 and Tables 2 and 3) reveal that the nylon textile in the three grindings had lower iDM and iNDF rates when compared to other treatments (p < 0.05) in the initial period of incubation. After 96 hours of incubation, all materials and grindings are likely to have similar rates where the differences between material, times and grinding may be due to the contamination of F57 and TNT textiles, as reported by Casali et al (2009) and Kuwahara et al (2015).…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations